Agro-morphological characterization of coloured rice genotypes for grain yield - Khatun, Most Morsada; Uddin, Md Kabir; Fakir, Md Solaiman Ali; Sarwar, A K M Golam (Bangladesh Journal of Botany, 2024)
Coloured rice (Oryza sativa L.) has become increasingly popular recently as a functional food because of its nutritional and health benefits. Effective selection criteria can be developed using characteristics contributing to genetic diversity in a particular group. This study characterised and evaluated the yield performance of 33 Bangladeshi coloured rice genotypes, 31 traditional and two checks, in the Kharif-1 (March - July) season of 2021 following standard cultivation procedure. Eight of the 33 genotypes did not flower during the Kharif-1 season; all other genotypes showed substantial differences in yield and yield attributing descriptors. Based on the yield attributing traits, the genotypes were divided into two broad clusters. In the Principal component analysis, the traits - flag leaf length and width, panicle length, number of primary and secondary branches, and filled grains per panicle, had maximum contribution towards the total variability. Among the genotypes, Bandarban-3 produced the maximum grain yield (32.62 g/hill), and some others had higher or comparable grain yield with the check Binadhan-20. These coloured rice genotypes might be added for multilocation trials to recommend for cultivation in the Aus season in Bangladesh. Bangladesh J. Bot. 53(4): 957-966, 2024 (December)